2014
DOI: 10.1186/1472-6874-14-125
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce postpartum stress in first-time mothers: a randomized-controlled trial

Abstract: BackgroundThe postpartum period can be a challenging time particularly for first-time mothers. This study aimed to assess two different interventions designed to reduce stress in the postpartum among first-time mothers.MethodsHealthy first-time mothers with healthy newborns were recruited from hospitals in Beirut, Lebanon after delivery. The two interventions were a 20-minute film addressing common stressors in the postpartum period and a 24-hour telephone support hotline. Participants were randomized to one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…As Osman et al concluded, when a combination of several means and tools is used for training and consulting, the effectiveness of intervention is increased and this could be one of the reasons that the supportive-educational intervention of this study is effective. In the study of Osman, when a combination of playing postpartum supportive film and 24-hour accountability phone call was presented to a group, the effectiveness of intervention was more than other groups receiving just one of them (9). However, the combination of educational methods and content in the form of a training package and giving it to mothers and husbands is not so hard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Osman et al concluded, when a combination of several means and tools is used for training and consulting, the effectiveness of intervention is increased and this could be one of the reasons that the supportive-educational intervention of this study is effective. In the study of Osman, when a combination of playing postpartum supportive film and 24-hour accountability phone call was presented to a group, the effectiveness of intervention was more than other groups receiving just one of them (9). However, the combination of educational methods and content in the form of a training package and giving it to mothers and husbands is not so hard.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the only interventional study that investigates postpartum stress with the help of specialized tools and based on stresses associated with child care, concerns related to physical health problems of women, and social support. The result of meta-analysis performed by Song et al suggest that other intervention studies have primarily measured stress in general and with the help of Perceived Stress Scale (PSS) and parental stress scale (9,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study points out that especially primiparous mothers may feel stressed by the changes and demands that childbirth imposes since they need to adapt to the new role. 17 Regarding the evaluation of perceived stress, it is highlighted that the items of the PSS-10 that had the highest frequency were "have been nervous or stressed" (2.63±53.58) and "have been angry because of things that were out of their control" (2.34±67.31). In a study that investigated the occurrence and control of stress in 30 sedentary and physically active pregnant women, it was verified that the majority, 93% had high levels of stress from sources intrinsic and extrinsic to gestation.…”
Section: -Positive Reassessmentmentioning
confidence: 99%
“…Mothers may feel exhausted and insecure regarding their capability to nurture an infant. 6 Overload of responsibilities and not having sufficient time to do things as they want have proved to be the most common stressors among fathers. 1 Their perspective is not taken into consideration very often.…”
Section: Introductionmentioning
confidence: 99%